Oxidized Cholesterol: Nanoparticles Containing Oxidized Cholesterol Deliver mRNA to the Liver Microenvironment at Clinically Relevant Doses (Adv. Mater. 14/2019). Issue 14 (2nd April 2019) - Paunovska, Kalina; Da Silva Sanchez, Alejandro J.; Sago, Cory D.; Gan, Zubao; Lokugamage, Melissa P.; Islam, Fatima Z.; Kalathoor, Sujay; Krupczak, Brandon R.; Dahlman, James E.
Abstract : Using mRNA to produce therapeutic proteins is a promising approach to treat genetic diseases. However, systemically delivering mRNA to cell types besides hepatocytes remains challenging. In article number1807748, James E. Dahlman and co‐workers report that a lipid nanoparticle formulated with oxidized cholesterol (instead of unmodified cholesterol) delivers Cre mRNA to hepatic endothelial cells and Kupffer cells at 0.05 mg kg −1 three‐to‐four times more potently than to hepatocytes.